Introducing Sub-Block Absorption to Improve the Performance of the Layered Indexless Indexed Flash Code - Fernandez, Proceso L, Jr (Archīum Ateneo, 2014)
Flash codes are used to encode and decode digital information in flash memory. One of the more well-known flash codes in literature is the Layered Indexless Indexed Flash Code (LILIFC). This study explores how to improve the performance of the LILIFC while staying true to its core. A new flash code is proposed, called the Layered Indexless Indexed Flash Code with Absorption (LILIFCWA), which introduces sub-block absorption to the LILIFC encoding function while retaining the original decoding function. Results from computer simulation showed marked improvements gained by LILIFCWA, with lower write deficiency ratios over variable flash memory sub-block sizes. An interesting correlation between the (LILIFCWA versus LILIFC) performance difference and cases involving a dominant bit update was also uncovered. These findings not only prove the superiority of the LILIFCWA over the LILIFC, but may also provide ideas to other researchers on how to improve other existing flash codes.